Discrete and combinatorial mathematics an applied introduction - Grimaldi, Ralph P. (Pearson Education, 2018)
The book is both complete and careful, and it continues to maintain its emphasis on algorithms and applications. Excellent exercise sets allow students to perfect skills as they practice. This new edition continues to feature numerous computer science applications-making this the ideal text for preparing students for advanced study.